Phonotop as an acoustic indicator for urban environment - Корниенко, С.В. (Sot͡s︡iologii͡a︡ goroda, 2023)
The relevance of the research topic is due to the need to introduce advanced urban planning solutions into practice to create a comfortable and safe urban environment. The purpose of the research work is to study the acoustic quality of the urban environment. Based on the analysis of various approaches to study of urban acoustic environment, a modern ecosystem trend has been identified: from reducing noise levels to creating a positive acoustic environment. For the first time, it is proposed to use the concept of “phonotop” to comprehensively assess the acoustic quality of the urban environment. Studies of phonotops can have significant benefits in understanding and improving the acoustic quality of megacities. Methods and tools used in the comprehensive study of urban soundscapes are summarized. To assess the acoustic mode of urbanized territories, a new indicator has been introduced — the urban acoustic index (UAI). Based on this indicator, classification of acoustic zones is proposed. The phonotops of the modern metropolis have been scientifically substantiated and investigated. The minimum value (UAI = 0.57) have a phonotop “production zone”, that associated with high noise pollution. The maximum value (UAI = 0.65) have a phonotop “socio-business specialized zone”, that can be explained by low noise pollution in this zone. According to the proposed classification of acoustic zones, most phonotops have a high acoustic quality of the urban environment. Key ways of creating positive sound landscapes have been systematized, that can be used for the development of specific proposals for the introduction of advanced urban planning solutions into practice to create a comfortable and safe urban environment